2016
DOI: 10.1371/journal.pone.0163499
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Various Health-Ratings with Geriatric Giants, Mortality and Life Satisfaction in Older People

Abstract: Self-rated health is routinely used in research and practise among general populations. Older people, however, seem to change their health perceptions. To accurately understand these changed perceptions we therefore need to study the correlates of older people’s self-ratings. We examined self-rated, nurse-rated and physician-rated health’s association with common disabilities in older people (the geriatric giants), mortality hazard and life satisfaction. For this, we used an age-representative population of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
10
0
3
Order By: Relevance
“…As verified with very old individuals [e.g., ( 10 , 14 , 17 , 39 )], it seems that also centenarians hold a weaker emphasis on their physical and functional status in the appraisal of their health condition. Previous studies that have shown discordance between objective and subjective health measures have associated it with the contribution of external and internal resources as optimism and perceived control ( 18 , 40 ). A positive SRH may reflect the greater importance of psychological adaptation in very advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…As verified with very old individuals [e.g., ( 10 , 14 , 17 , 39 )], it seems that also centenarians hold a weaker emphasis on their physical and functional status in the appraisal of their health condition. Previous studies that have shown discordance between objective and subjective health measures have associated it with the contribution of external and internal resources as optimism and perceived control ( 18 , 40 ). A positive SRH may reflect the greater importance of psychological adaptation in very advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…yapmış olduğu çalışmada cinsiyet ile özbakım gücü arasında istatis- tiksel olarak anlamlı fark olduğu belirlenmiştir. [16] Bayan yaşlılarda özbakım gücü daha yüksek bulunmuştur. Genellikle bayanların gençlik döneminde de erkeklere oranla bakımlarında daha düşkün olmaları ve bakımlarını kendilerinin yapmaları yaşlılık döneminde de bayanların özbakımın yüksek olmasının nedeni olabilir.…”
Section: Discussionunclassified
“…Gait disorders affect a significant number of communitydwelling older adults and have recently been highlighted as a potential indicator of later cognitive decline. Gait disorders are believed to affect up to one third of older adults aged > 70 years and may be divided based on the particular sensorimotor deficit involved: (i) lower level gait disorders such as osteoarthritis, (ii) mid-level gait disorders which result from a focal neurological lesion such as that seen in Parkinson's Disease and (iii) higher level gait disorders with no demonstrable deficits in the pyramidal/extrapyramidal/sensory or cerebellar systems (and may be particularly related to cerebrovascular disease) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%